Shaping Tax Career Interest Through Self-Efficacy and Competence: The Moderating Role of Job Opportunities for Muslim Tax Volunteers - Putri, Ravayna Yulia; Fakhriyyah, Dewi Diah; Sudaryanti, Dwiyani (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
The taxation sector increasingly demands skilled professionals to support national revenue and economic growth. However, students’ interest in pursuing a tax career remains low due to perceptions of complexity and limited professional exposure. This study aims to examine the influence of Tax Self-Efficacy and Professional Competences on Tax Career Interest, with Job Opportunities as a moderating variable. A quantitative explanatory approach was employed, surveying 126 students participating in the Tax Volunteer Program at the Directorate General of Taxes East Java III Regional Office. Data were collected via online questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results reveal that Professional Competences have a positive and significant effect on Tax Career Interest, whereas Tax Self-Efficacy alone does not. Job Opportunities significantly strengthen the relationship between Tax Self-Efficacy and Tax Career Interest but do not moderate the effect of Professional Competences. These findings highlight the dominant role of personal competences in shaping career interest and the importance of integrating experiential learning through tax volunteer programs to enhance students’ motivation and career readiness. The study provides practical implications for educational institutions and tax authorities in designing programs that combine professional training with real-world experience to foster human resource development in the taxation sector.